2014
DOI: 10.1074/jbc.m113.533042
|View full text |Cite
|
Sign up to set email alerts
|

Matricellular Protein Cyr61 Bridges Lysophosphatidic Acid and Integrin Pathways Leading to Cell Migration

Abstract: Background: The molecular mechanism of smooth muscle cell (SMC) migration, a crucial event in atherosclerosis, is not well understood. Results: The de novo matricellular protein Cyr61 bridges lysophosphatidic acid (LPA) and integrin pathways, activating focal adhesion kinase (FAK) and leading to cell migration. Conclusion:The LPA-Cyr61-integrin-FAK axis controls SMC migration. Significance: This study provides new insights into mechanisms underlying cell migration-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…49 Interaction of Cyr61 with integrin increases FAK phosphorylation, which enhances AKT activation. 50 AKT has been a critical mediator of cell proliferation, survival and metastasis in a variety of cell types. 51 Results of the present study show that AMOT downregulation increases FAK and AKT phosphorylation, which are inhibited by Cyr61 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…49 Interaction of Cyr61 with integrin increases FAK phosphorylation, which enhances AKT activation. 50 AKT has been a critical mediator of cell proliferation, survival and metastasis in a variety of cell types. 51 Results of the present study show that AMOT downregulation increases FAK and AKT phosphorylation, which are inhibited by Cyr61 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Cyr61 seems to be the long-missing, important extracellular mediator in the PDGF pathway. Our recent study has demonstrated that Cyr61 is a key mediator for lysophosphatidic acid-induced cell migration (51). One previous article showed that Cyr61 mediates thrombin-induced cell proliferation (52).…”
Section: Discussionmentioning
confidence: 99%
“…These same integrin/ECM signaling proteins can also influence YAP/TAZ regulation [20,43,146,151,152]. For example, in skeletal stem cells the membrane-anchored metalloproteinase MT1-MMP was found to activate the β1-integrin/RHO GTPase signaling cascade, which triggered the nuclear accumulation of YAP/TAZ and promoted skeletal stem cell lineage commitment [150].…”
Section: Yap/taz As a Signaling Networkmentioning
confidence: 99%